COST OF CAPITAL PADA BANK SYARIAH MANDIRI PERIODE 2004-2008 - Indra Setyawan; Apriani Dorkas Rambu Atahau (University of Merdeka Malang, 2010)
The growth of Islamic or Syariah banking had been remarkable. It was not onlyoccuring in count ries where the Moslems were majorit y but also in count ries where Moslemswere minority. Syariah banking itself had a specif ic characterist ic known as prof it -and-losssharing system. This prof it-and-loss sharing system was dif ferent f rom interest -based systemused by convent ional banks. Prof it-and-loss sharing system implementat ion had a significant impact on the cost of capital calculat ion in Islamic banks. This research described thecalculat ion of capital cost in Bank Syariah Mandiri as one of Islamic (syariah) banks. The aimof the study was to give view about the capital cost of Mandiri syariah bank in Indonesia. Thedata were taken f rom Mandiri Syariah banks f inancial report during f ive consecut ive years.The data were analyzed by using t rend analysis. Based on t rend analysis in every componentof cost of capital, it was concluded that the cost of capital of Bank Syariah Mandiri syariahbank tended to decrease due to the decreasing t rend of its cost of debt .